Molecular characterization of invasive serogroup Y Neisseria meningitidis strains isolated in the Latin America region - Abad, Raquel (2009)
Fil: Abad, Raquel. Instituto de Salud Carlos III. Centro Nacional de Microbiología. Reference Laboratory for Meningococci; España.